Obtaining sustainable raw forms for wheat breeding (Eurasian Journal of Ecology, 2018)
Using traditional methods of breeding and genetic research, such asmutagenesis, backcrossing selection and distant hybridization obtainedgenetically improved recombinant forms of soft wheat. Studied the level offertility of hybrids of common wheat with wild species with T. timopheeviand the dependence the fertility of hybridson the direction of crosses andgenotype varieties.In the study of reciprocal hybrids F1, obtained by crossing wheat with wild species – T. timopheevi found clear differences inthe percentage of the appearance of the grains. The results showed thatthe use of wild species with reciprocal crossing it with a soft wheat as aparent component genomes increases compatibility. For hybrids derivedfrom crosses with T. timopheevi soft wheat characteristic heteroplasmiccondition: simultaneously present copies of the wild (motherly) and wheat(paternal) types. Using mutants obtained using chemical compounds require a study of the genetic nature of changes occurring that is of greatimportance for the selection of effective and specific action of mutagens,and to broaden and deepen understanding of the nature of the evolutionof wheat. These mutants under the action of mutagens can be successful,serve as the progenitors of new high-yield varieties.On the basis of grade Kazakhstanskaya 126 using sources of foreigngenes, a series of isogenic lines genes Hg, Bg, C, PP, Eg, Hp, B, Rht, Pc, W,Ra.A method for identifying monosomic and disomnyh plant phenotypeby marker gene expression.Key words: selection, distant hybridization, chemical mutagenesis,isogenic lines, replacement of chromosomes, variety, chromosome wheat.